Coastal ecotourism in The Gambia: Effects of sustainability communication on environments and rural livelihoods - Pauline Attemene; Irit Eguavoen (University of Bonn, Center for Development Research (ZEF), 2017)
This paper is based on a field study carried out in 2015 in two coastal ecotourism areas in The Gambia - Kartong and Tanji. The study investigated sustainability communication by tourism service providers in the context of climate change and ecovillage design education (EDE). With an inclusive approach to investigate communication, which integrates words, writing, actions as well as individual and collective behavior, the methodology was based on participant observation, semi-structured interviews with tourism service providers, local population, as well as the examination of documents. It has attended to answer the following question: how do ecotourism providers communicate sustainability issues in key areas, including education, marketing and networks activities in Kartong Ecotourism Area and Tanji Bird Reserve within the context of climate change? The findings highlight that sustainability-related ecotourism communication may help to prevent environmental degradation through encouraging more sustainable practices as a result of training resident communities, especially the youth. Sustainability communication in the case studies was not geared toward eco-tourists despite the fact that a small number of more knowledgeable business owners have included climate change and sea level rises in their communication towards potential customers. Findings illustrate that these service providers in tourism had succeeded in engaging young people and wetland communities in environmental action and in the production as well as the promotion of energy-efficient cooking and building technologies. Local income generation activities, such as oyster farming have been supported by ecotourism.
Keywords: 330; communication; education; ecotourism; West Africa